Profil Plasma Nutfah dan Jenis Penyakit Pisang Lokal asal Pandeglang Banten - Nani Maryani; Susilawati Dewi; Indah Juwita Sari; Rida Oktorida Khastini (LPPM, 2019)
Banana is the most favorite fruits in the world. Indonesia is in the center of origin and diversity of banana in Southeast Asia. Banten is one of the most banana producer in Indonesia. However, no information on banana diversity and its associated disease available from this province. In this paper, we explored Kabupaten Pandeglang in its diversity of banana and its associated disease. Eleven local banana germplasm were identified with their associated disease. Fusarium wilt, Sigatoka, and Blood disease are the most common diseases found on those varieties. Seven local banana germplasm are described in this paper. These information are very important to preserved biodiversity of Indonesia and will be useful for future food security and sustainability.